COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN UMKM BERKELANJUTAN: MODEL KONSEPTUAL BERDASARKAN SYSTEMATIC LITERATURE REVIEW - Said Mustafa; Novelma Lastri; Variza Aditiya; Dwi Hartutik; Suprasman Suprasman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in national economic development by contributing to economic growth, employment generation, and poverty reduction. Nevertheless, MSMEs continue to face significant challenges, including limited access to finance, digital transformation, human resource capability, innovation, and long-term business sustainability. These challenges require a collaborative governance approach that involves government, private sector, academia, financial institutions, communities, and civil society in a shared decision-making process. This study aims to synthesize the existing body of knowledge on collaborative governance in sustainable MSME development through a systematic literature review. The study adopts the Systematic Literature Review (SLR) method by analyzing scholarly articles indexed in Scopus, Web of Science, and Google Scholar. The review focuses on governance models, stakeholder roles, enabling factors, implementation challenges, and future research directions. The findings reveal that successful sustainable MSME development is strongly influenced by stakeholder trust, facilitative leadership, institutional design, active participation, and digital technology integration. Furthermore, multi-stakeholder collaboration enhances innovation capacity, market access, competitiveness, and business resilience. This review contributes by providing a comprehensive synthesis of collaborative governance literature in sustainable MSME development and identifying research gaps that may guide future theoretical and empirical studies. Keywords: Collaborative Governance, MSMEs, Sustainable Development, Stakeholder Collaboration, Systematic Literature Review.   Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) merupakan pilar utama perekonomian nasional yang berkontribusi terhadap pertumbuhan ekonomi, penciptaan lapangan kerja, dan pengurangan kemiskinan. Namun demikian, berbagai tantangan seperti keterbatasan akses permodalan, transformasi digital, kapasitas sumber daya manusia, inovasi, serta keberlanjutan usaha masih menjadi kendala dalam pengembangan UMKM. Kondisi tersebut mendorong perlunya pendekatan collaborative governance yang melibatkan pemerintah, sektor swasta, akademisi, komunitas, lembaga keuangan, dan masyarakat dalam suatu proses pengambilan keputusan yang kolaboratif. Artikel ini bertujuan untuk mensintesis perkembangan penelitian mengenai penerapan collaborative governance dalam pengembangan UMKM berkelanjutan melalui kajian literatur. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan menganalisis artikel ilmiah bereputasi yang diperoleh dari basis data Scopus, Web of Science, dan Google Scholar. Analisis difokuskan pada konsep, model, aktor, faktor keberhasilan, tantangan implementasi, serta arah penelitian masa depan. Hasil sintesis menunjukkan bahwa keberhasilan pengembangan UMKM berkelanjutan sangat dipengaruhi oleh tingkat kepercayaan antarpemangku kepentingan, kepemimpinan fasilitatif, desain kelembagaan, partisipasi aktif, serta integrasi teknologi digital. Selain itu, kolaborasi multipihak mampu meningkatkan kapasitas inovasi, akses pasar, daya saing, dan ketahanan UMKM dalam menghadapi perubahan lingkungan bisnis. Penelitian ini memberikan kontribusi konseptual berupa pemetaan perkembangan kajian collaborative governance dalam pengembangan UMKM berkelanjutan sekaligus mengidentifikasi kesenjangan penelitian yang dapat menjadi agenda penelitian selanjutnya. Kata kunci: Collaborative Governance, UMKM, Sustainable Development, Stakeholder Collaboration, Systematic Literature Review